2004
DOI: 10.1097/01.hjr.0000136414.40017.10
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sustainability of exercise and health-related quality of life outcomes following home or hospital-based cardiac rehabilitation

Abstract: This follow-up study suggests that low-risk patients whose CR is initiated in the home environment may be more likely to sustain positive physical and psychosocial changes over time than patients whose program is initially institution-based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(149 citation statements)
references
References 17 publications
6
142
1
Order By: Relevance
“…These include early discharge, less complications for inpatients, cost-effective management, and better achievement in post discharge drug compliance and better quality of life [12][13][14] . Being autonomous and independent, CV patients usually achieve higher self-confidence, which, in turn, could encourage healthier life style and better productive life [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…These include early discharge, less complications for inpatients, cost-effective management, and better achievement in post discharge drug compliance and better quality of life [12][13][14] . Being autonomous and independent, CV patients usually achieve higher self-confidence, which, in turn, could encourage healthier life style and better productive life [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al 45 Two cardiac rehabilitation programs were conducted for 6 months: one group at home and the other in the hospital. After the program, individuals were instructed to continue aerobic exercises for at least 5 times/week (40-75 min).…”
mentioning
confidence: 99%
“…Many published studies have revealed improvements in the health-related QOL of patients with CHD after CR programs, either the residential model or ambulatory CR (ACR). [12][13][14][15][16][17][18][19][20][21][22][23] The aim of this study was to evaluate the impact of different models of CR, residential vs ambulatory, on healthrelated QOL according to the exercise capacity of patients with CHD. …”
mentioning
confidence: 99%